A robust possibilistic-M/G/c queuing model for a hub location problem with a ring topology of a backbone network - Eghbali, Maryam; Jolai, Fariborz; Tavakkoli-Moghaddam, Reza (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
In a telecommunication industry as one of the oldest users of the hub network concept, networks do not operate on a complete hub network and hubs can configure different structures. A ring topology, especially synchronous optical network (SONET) rings in telecommunication networks, has increasing importance because of the self-healing properties associated with them. In this paper, a novel model is presented for a hub location problem with a ring topology of a hub network under the inherent uncertainty of input data. In this model, hubs are considered as M/G/c queuing system. To solve the model, a new hybrid solution methodology is introduced by combining a robust possibilistic programming approach and queuing theory. To study the behavior of the robustness of the proposed model, computational experiments are considered for a number of test problems. A comparative analysis is carried out to show the performance and superiority of the robust approach over the basic possibilistic chance constrained programming approach.